2013
DOI: 10.4162/nrp.2013.7.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin C and E supplementation on oxidative stress and liver toxicity in rats fed a low-fat ethanol diet

Abstract: We compared the preventive capacity of high intakes of vitamin C (VC) and vitamin E (VE) on oxidative stress and liver toxicity in rats fed a low-fat ethanol diet. Thirty-two Wistar rats received the low fat (10% of total calories) Lieber-DeCarli liquid diet as follows: either ethanol alone (Alc group, 36% of total calories) or ethanol in combination with VC (Alc + VC group, 40 mg VC/100 g body weight) or VE (Alc + VE group, 0.8 mg VE/100 g body weight). Control rats were pair-fed a liquid diet with the Alc gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…However, the effect of α-tocopherol on plasma homocysteine level was inconsistent. A recent study had also shown that α-tocopherol reduced serum homocysteine in rats fed methionine and cholesterol diet [17], but it was ineffective in rats fed a low-fat ethanol diet [20]. The ineffective effect of α- tocopherol on hyperhomocysteinaemia was also reported in humans [26,35].…”
Section: Discussionmentioning
confidence: 97%
“…However, the effect of α-tocopherol on plasma homocysteine level was inconsistent. A recent study had also shown that α-tocopherol reduced serum homocysteine in rats fed methionine and cholesterol diet [17], but it was ineffective in rats fed a low-fat ethanol diet [20]. The ineffective effect of α- tocopherol on hyperhomocysteinaemia was also reported in humans [26,35].…”
Section: Discussionmentioning
confidence: 97%
“…Experimental treatment with ethanol diet induces oxidative stress and consequent liver toxicity, independent of the levels of fat in diet, and that tocopherol supplementation has a protective effect against oxidative stress and liver toxicity in rats [20]. Shirpoor et al [21] demonstrated that treatment with vitamin E induces a significant amelioration of brain atrophy and DNA damage in the offspring of female Wistar rats that received ethanol during gestation and seven days of lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants play an important role in preventing molecular and cellular damage caused by free radicals. Antioxidants such as vitamin C and N-acetyl cysteine have been shown to attenuate acute EtOH toxicity by lowering lipid peroxidation and GSH depletion up to a certain extent (Lee et al, 2013;Wang et al, 2006). PQQ has been shown to reduce acetaldehyde levels in blood after EtOH ingestion in rats (Hobara et al, 1988).…”
Section: Discussionmentioning
confidence: 99%